2001
DOI: 10.1046/j.1365-2109.2001.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of animal size on the ability of Haliotis midae L. to utilize selected dietary protein sources

Abstract: The effect of animal size on the qualitative protein requirements of two size classes of Haliotis midae L. was assessed by feeding 12 semi‐purified single protein test diets (20% protein, 6% lipid) to juvenile and young adult animals (10–20‐ and 40–50‐mm initial shell length). The protein sources selected for the trial comprised four fishmeals, casein, spirulina, abalone viscera silage, brewery waste, torula yeast, carcass, sunflower and cotton seed meals. The results indicated that in terms of growth and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
(35 reference statements)
3
16
3
2
Order By: Relevance
“…The combination of fishmeal and spirulina produced the highest mean weight and shell-length gain in the trial, highlighting the nutritional value of these two high-protein ingredients for abalone at the weaning stage; this was probably due to the contribution of spirulina toward the nutrients that may have been lacking in the fishmeal-only feed (Dlaza et al 2008). These results are consistent with those of Bautista-Teruel et al (2003) and Shipton and Britz (2001), who found that juveniles fed a formulated diet containing spirulina in combination with fishmeal grew faster than those fed diets containing spirulina and soya meal only. This study was not designed to test the effect that protein level had on growth as variables other than total protein content, such as carbohydrate content, total digestible energy, diet presentation, etc., also differed between Abfeed ® -S34 and the experimental diets.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The combination of fishmeal and spirulina produced the highest mean weight and shell-length gain in the trial, highlighting the nutritional value of these two high-protein ingredients for abalone at the weaning stage; this was probably due to the contribution of spirulina toward the nutrients that may have been lacking in the fishmeal-only feed (Dlaza et al 2008). These results are consistent with those of Bautista-Teruel et al (2003) and Shipton and Britz (2001), who found that juveniles fed a formulated diet containing spirulina in combination with fishmeal grew faster than those fed diets containing spirulina and soya meal only. This study was not designed to test the effect that protein level had on growth as variables other than total protein content, such as carbohydrate content, total digestible energy, diet presentation, etc., also differed between Abfeed ® -S34 and the experimental diets.…”
Section: Discussionsupporting
confidence: 94%
“…The growth and soft-body tissue to shell 1.76 ± 0.14 ab 32.26 ± 1.95 ab 0.91 ± 0.02 a 2.38 ± 0.14 a 83.0 ± 5.5 a 1 Statistical analyses were carried out on log-transformed data for percentage mean survival and mean SB/S mass ratio, although the untransformed data are presented here 2 Survival data and analysis presented here include data from Days 5 to 27 only mass ratios of abalone that were fed the spirulina-only diet was relatively lower than the diets containing fishmeal. This contrasts to the findings of Britz (1996a) and Shipton and Britz (2001) who fed a spirulina-based diet to larger (>14 mm shell length) H. midae and observed that their relative growth and feed conversion rates were only slightly lower than those fed a fishmeal-based diet. This difference might be due to variations in the nutritional content of the spirulina, because different sources of spirulina were used in these studies.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Mais recentemente [23], avaliaram o efeito de 12 diferentes fontes protéicas semi-purificadas na dieta de peixes (Haliotis midae L.) para consumo humano. As fontes protéicas incorporadas à ração contendo 20% de proteína e 6% de lipídio foram: 4 rações comerciais, caseína, spirulina, víscera ensilada de peixe (abalone), resíduo de fabricação de cerveja, levedura torula, carcaça do processamento de peixe, semente de girassol e caroço de algodão.…”
Section: Quadro 2 Parâmetros De Controle De Qualidade Para Farinhas unclassified
“…Por serem uma fonte rica em nutrientes, as vísceras de bovinos [1,14], aves [1,13], peixes [1,13], moluscos e crustáceos marinhos [1,7,11,23,25] são muito utilizadas na produção de farinha de carne, como componente de ração para o consumo de aves, peixes, e animais domésticos (de consumo e ou ornamentais) [13].…”
Section: -Introduçãounclassified